Investigation into the effect of delays between printed layers on the mechanical strength of inkjet 3DP mortar. (January 2020) - Shakor, Pshtiwan; Nejadi, Shami; Paul, Gavin
Abstract: Currently, additive manufacturing have enabled to fabricate the three-dimensional models. 3D-Printing technique is a multipurpose process for producing structural members using a sequential layering approach. The "feature quality" of 3DP specimens can be improved by optimising the build constraints. In this paper, a mortar mix powder-base has been prepared that consists of cementitious materials. Experiments are conducted to investigate the effects of different delays in printing time on the mechanical properties of the scaffolds. It has been shown that the compressive stress and strength of printed specimens with a delay of 200 ms were greater than specimens with other delay values.